Methods for evaluating HER2 status in breast cancer: comparison of IHC, FISH, and real-time PCR analysis of formalin-fixed paraffin-embedded tissue - Olsson H; Jansson A; Holmlund B; Gunnarsson C (Dove Medical Press, 2013)
Hans Olsson,1,2 Agneta Jansson,3 Birgitta Holmlund,3 Cecilia Gunnarsson2,4 1Molecular and Immunological Pathology, Department of Clinical and Experimental Medicine, Faculty of Health Sciences, Linköping University, Linköping, Sweden; 2Department of Clinical Pathology and Clinical Genetics, Östergötland County Council, Linköping, Sweden; 3Division of Oncology, Department of Clinical and Experimental Medicine, Faculty of Health Sciences, Linköping University, Linköping, Sweden; 4Division of Genetics, Department of Clinical and Experimental Medicine, Faculty of Health Sciences, Linköping University, Linköping, Sweden Abstract: The human epidermal growth factor receptor 2 gene (HER2) is amplified in approximately 15%–20% of all breast cancers. This results in overexpression of the HER2 protein, which is associated with worse clinical outcomes in breast cancer patients. Several studies have shown that trastuzumab, a monoclonal antibody that interferes with the HER2/neu receptor, can improve overall survival in patients with HER2-positive breast cancer. Immunohistochemistry (IHC), combined with different methods for in situ hybridization, is currently used for routine assessment of HER2 status. The aim of the present study was to determine whether real-time polymerase chain reaction (PCR) can serve as a supplementary method for evaluation of HER2 status in primary breast cancer. For this purpose, 145 formalin-fixed paraffin-embedded primary breast cancer samples were tested by real-time PCR amplification of HER2, using amyloid precursor protein as a reference. The results were compared with HER2 status determined by fluorescence in situ hybridization (FISH) and IHC. The specificity, sensitivity, and reproducibility of real-time PCR were evaluated, and a comparison of formalin-fixed and fresh-frozen samples was performed. This showed concordance of 93% between real-time PCR and FISH, and 86% between real-time PCR and IHC. Therefore, we suggest that real-time PCR can be a useful supplementary method for assessment of HER2 status. Keywords: 17q, breast cancer, HER2, real-time PCR